E-Clinic System (ECS) / Rossuryaindah Maarof - Rossuryaindah, Maarof (2004)
As we move towards a knowledge-driven economy in 21 st century, healthcare providers are nowadays being forced to streamline operation through more efficient and cost effective office procedures. Automating these tasks results in time and materials, providing a positive return on investment. E-Clinic System (ECS) is windows based application built to assist clinical practitioners with their daily practice. The objective is to automate manual procedures that are currently practiced in a clinic. Prototyping Model is adopted to allow the designer to build a prototype, test and modify it, and through an iterative process to complete the final product. The development environment for ECS is Microsoft Windows 2000 Professional and Visual Basic 6 is used as its programming languages. While Microsoft Access 2000 and ADO as the Database Management System (DBMS) that is the most efficient to support all the backend processes of ECS. As a conclusion, ECS is used to assist the clinic management by automating or assisting in repetitive and time-consuming tasks. It is enabling and empowering the tool in managing clinic information.